Artificial Intelligence in Islamic Religious Education: A PRISMA-Based Review and the SEI-CHAT Framework - Muhamad Arif; Mohd Kasturi Nor Abd Aziz; Hazman Hassan; Yahya Fikri; Mohamed Zekkari; Bela Vita Rismawati (CV FOUNDAE, 2026)
Although Artificial Intelligence (AI) has been rapidly integrated into contemporary education, little scholarly attention has been paid to its implications on the epistemological, theological, and cultural foundations of Islamic Religious Education (IRE). This study aims to systematically analyze the implementation patterns, effects, and challenges of AI on IRE learning in the digital age. This study was conducted through a Systematic Literature Review (SLR) method by using Publish or Perish software to retrieve relevant articles from Scopus, Web of Science, Semantic Scholar, and Google Scholar databases on 01 August 2025, using the Boolean search query: (